Development of multimode fiber optic-based ethanol sensor using nanocomposite sensitive layer - Ali, Ali Mohammed (2017)
Optical fiber sensors have been gaining popularity on a wide scale over the past two decades as the call for highly efficient, miniaturised and versatile sensing devices are rapidly becoming a necessity. This research focused on the design and analysis of a standard multi-mode fiber optic to be used as a sensor for the detection of aqueous ethanol. Using multi-mode fiber optic (MMF) sensor in the process of detecting liquid required a process to amend the fiber by mode of tapering in order to increase the effectiveness of the sensor for sensing. The focus of this project is to increase the evanescent waves of the sensor and to increase the absorption rate and sensitivity of the sensor. It was done by using Au (gold) and Pd (palladium) as the nanocomposite coating layer. In this thesis, the effect of Au layer on the fiber, Pd layer on the fiber and the combination of both of Au and Pd as a nanocomposite are investigated for the sensor performance. Au and Pd have emerged as leading materials in a wide variety of applications, including chemical sensors, due to their exceptional thermal, optical and mechanicalproperties. The combination of Au and Pd are able to enhance the chemical reaction with ethanol, resulting in sensing capability of the sensor. Moreover, increments of the sensitivity were observed by coating a nanocomposite layer of the Au and Pd on the tapered fiber. The study dealt with five sensors with different coating ratios. The first sensor was coated by nanocomposite layer of Au and Pd with ratio 2 to 1 respectively. The second sensor was coated with a compound of 1 to 0.7 ratio of Au to Pd. The third sensor was coated with 1 to 1 ratio of the compound Au and Pd respectively. The fourth sensor is coated by 1 to 2 ratio of Au to Pd. The last sensor was coated with Au and Pd ratio of 1 to 3 respectively. All the nanoparticle layer were deposited on the tapering region using drop casting technique, after the sensors were annealed at 70C. The developed sensors demonstrated high sensitivity at 0.074/vol % and response and recovery times of approximately 13 and 9 seconds, respectively. The achievements of this study are to use a large diameter tapered as a sensitive sensor toward ethanol and to apply Au and Pd mixture to tapered fiber toward ethanol detection.